Standardization of Soil Conservation Practices - Rama Rao, MSV (Journal of Soil and Water Conservation, 2022)
The main object of this paper is to see how far can standardize practices in soil conservation. I knoxv it is not possible to lay down unifortn Yardsticks for soil conservation practices in such a big country as India but it would appear possible to lav doun certain limits. The effect that man mav have on his environment is often profound. The effect is not alivays good. Injudicious land use is one of them and history is full of such examples and their detrimental results. are thankful to Dr. Bennett of U.S.A. and manv other who have dwelt on the subject of erosion some scientifically and some thrillingly that at present a flood of light has been on the subject. They save sometimes war is a blessing in disguise. S80n after the last war India faced with deficit food and soil conservation presented itself as one way to solve the puzzle next to irrigation. all know that research is the main plank on which the soil conservation exten- Sion work has to bank upon Government of India's interest in the subject of soil conser- vation in general and research work in particular has been evident in the formation of the Central Soil Conservation Board, establishment of a few Research Stations to solve typical regional problems and giving aid to States in a number of projects. This does not mean that there has been any spectacular achievement. It only means that in many regions soil conservation is in its preparatory stages and that the actual execution of works is still in its beginnings in many States. All we could say is that the movement is gathering strength and is penetrating to the rural areas. penetrating to the rural areas.